Evaluating the hierarchical, hygroscopic deformation of the Daucus carota umbel through structural characterization and mechanical analysis. (November 2019) - Zhang, Pengli; Chen, Po-Yu; Wang, Bingfeng; Yu, Rentong; Pan, Haobo; Wang, Bin
Graphical abstract: Abstract: Many physically immobile plants develop passive yet ingenious strategies for active seed dispersal through self-deformation in response to external stimuli, such as humidity. These hygroscopic deformations are usually driven by the internal heterogeneous architecture, which provides valuable, inspiring information for the development of novel actuating systems. The Daucus carota compound umbel is an interesting structure showing a distinct hygroscopic deformation that operates at hierarchical levels among these plants. Here, we investigate the structure of the primary and secondary rays of the umbel associated with their deformation through mechanical analyses. We reveal that through controlling both the cellulose microfibril angle (MFA) and lignification, the multi-level bending behavior of the umbel is achieved, which contributes to efficient seed protection and dispersal. The primary rays generally show more significant bending curvature changes than the secondary rays, and within each level, the outer rays exhibit a larger motion amplitude than the middle and inner rays. Mechanical testing and theoretical analysis support that adjusting the lignin content within the ray structure compensates for the effect of the small differences in cellulose MFA on its bending behavior, which contributes to the overall hygroscopic deformation. Findings also show that the primary outer ray can generate reaction forces that are more than 700 times its weight, which is higher than that for the pine cone scales. The new insights from this work are instructive for bioinspired designs of complex, self-deforming structures and devices. Statement of Significance: The carrot ( Daucus carota ) compound umbels exhibit a unique hierarchical, hygroscopic deformation for seed dispersal among immobile plants. In this work, we elucidate that the multi-level bending behavior of the umbel is achieved through manipulating the cellulose microfibril angle (MFA) and lignification of the primary and secondary rays for the first time. We also discover that adjusting the degree of lignification compensates for the effect of small cellulose MFA differences on the bending behavior theoretically and experimentally. The primary outer rays deform in a highly efficient manner, in which reactions forces about more than 700 times its weight are generated. The findings presented are instructive for bioinspired designs of complex, self-deforming structures and devices.